1996
DOI: 10.1177/095148489600900105
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Maternal Mortality in Rural China

Abstract: A case-control study of maternal mortality was conducted in selected rural areas of two provinces in China: Henan province, which has a relatively lower socio-economic status and higher maternal mortality rates, and Jiangsu province with higher socio-economic status and lower maternal mortality rates. The major cause of maternal mortality in the two provinces was postpartum hemorrhage and the largest proportion of deaths occurred on the road between the women's home and the health care facility. Results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…Although economic factors associated with maternal mortality are widely documented (Brieger, Luchok, Eng, & Earp, 1994;Forssas et al, 1999;Li & Fottler, 1996;Taguchi et al, 2003), we argue that the influence of economic factors is complicated. When the economy develops to a certain extent, other related factors will influence maternal mortality much more.…”
Section: Factors Contributing To Maternal Mortalitymentioning
confidence: 88%
“…Although economic factors associated with maternal mortality are widely documented (Brieger, Luchok, Eng, & Earp, 1994;Forssas et al, 1999;Li & Fottler, 1996;Taguchi et al, 2003), we argue that the influence of economic factors is complicated. When the economy develops to a certain extent, other related factors will influence maternal mortality much more.…”
Section: Factors Contributing To Maternal Mortalitymentioning
confidence: 88%
“…In addition to the lack of access to public‐funded services, unfamiliarity with the new environment, lack of a social support network, and unawareness of warning signs of complications because of illiteracy may add further difficulties to the migrating population, especially at critical times such as emergency in childbirth. A case–control study of maternal mortality conducted in the Chinese provinces of Henan and Jiangsu found that the main cause of maternal mortality was postpartum haemorrhage, the largest proportion of deaths occurred on the way between the women’s home and the healthcare facility; and women’s low socio‐economic status, lack of knowledge, and lack of access to quality maternal care facilities were important determinants of maternal deaths 14 . Ding and Zhang 5 reviewed 5984 cases of maternal deaths collected in a 7‐year collaborative surveillance programme in China and found that the main causes of maternal deaths were obstetric haemorrhage, pre‐eclampsia, heart diseases, amniotic fluid embolism, puerperal infection, and hepatic diseases, and these six causes constituted 81.6% of the total.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in China suggested that home delivery, lack of prenatal care, low income, illiteracy, poor quality of obstetric care and minority nationality were associated with an increased risk for maternal death 7,16,27,40 . In 1992, in 40 impoverished counties in Yunnan, 61% of the 450 maternal deaths occurred at home, 30% at a health facility and 9% on the way to hospital 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in China suggested that home delivery, lack of prenatal care, low income, illiteracy, poor quality of obstetric care and minority nationality were associated with an increased risk for maternal death. 7,16,27,40 In 1992, in 40 impoverished counties in Yunnan, 61% of the 450 maternal deaths occurred at home, 30% at a health facility and 9% on the way to hospital. 16 Pregnancy outside China's family planning guidelines is also a risk factor for maternal death, with 78.9/100 000 live births among women whose pregnancies were within the guidelines versus 135.6/100 000 for those who were not.…”
Section: Significance In Relation To Previous Researchmentioning
confidence: 99%